Kajian Literatur Religiusitas dan Influencer Marketing terhadap Keputusan Pembelian Skincare Halal Somethinc pada Konsumen Muslim - Mutiara Salsabila; Moh. Mukhsin (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2026)
The skincare industry in Indonesia is experiencing rapid growth as public awareness of the importance of skincare increases and the use of social media as a source of product information becomes more widespread. In the Muslim consumer segment, religiosity and influencer marketing are factors that are widely studied because they have the potential to influence the purchase decisions of halal products. This study aims to analyze the role of religiosity and influencer marketing on the purchasing decisions of Somethinc halal skincare among Muslim consumers thru a literature review approach. The method used is a literature review by examining various national and international scientific publications obtained from Google Scholar, ScienceDirect, Emerald Insight, as well as Sinta and Scopus indexed journals for the period 2021–2026. The selected articles are relevant to the themes of religiosity, influencer marketing, Muslim consumer behavior, and purchasing decisions for halal skincare products. Data analysis was conducted using content analysis and comparative analysis to identify patterns in findings across studies. The study results show that religiosity contributes to shaping the values, attitudes, and considerations of Muslim consumers in choosing halal skincare products. In addition, influencer marketing thru aspects of credibility, attractiveness, and communication skills of the influencer also influences consumer perception and trust toward the product. These findings affirm the interaction of internal and external factors in the formation of halal skincare purchase decisions and enrich the study of Muslim consumer behavior and digital marketing.